2012
DOI: 10.1111/j.1365-2621.2012.03058.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences of food matrices on cytotoxicity of asiatic acid in mammalian cell models

Abstract: This study investigated the cytotoxicity of asiatic acid (AA) encapsulated in different protein-carbohydrate matrices in human colon adenocarcinoma SW620, human hepatoblastoma HepG2 and diploid monkey kidney cells (Vero). Mungbean protein concentrate (MPC) and mungbean protein hydrolysate (MPH) in lactose (L) or lactose-maltodextrin (LM) mixture, were used to fabricate matrices encapsulating AA during lyophilisation. The cytotoxicity of AA was in a dose-dependent manner for HepG2 and SW620 cells, but not for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This study showed that antioxidative MPH from tryptic hydrolysis, which had a fairly high surface charge of (−)30 mV, could reduce micellisation of AA in the aqueous phase. The MPH–AA co‐aggregates may help to increase cellular uptake via passive diffusion by controlling the particle size to around 300 nm (Wongekalak et al ., ; Jirasripongpun et al ., ). The degree of co‐aggregation between MPH and AA was found to be dependent on their ratio and the type of carbohydrate in the bulk aqueous phase.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This study showed that antioxidative MPH from tryptic hydrolysis, which had a fairly high surface charge of (−)30 mV, could reduce micellisation of AA in the aqueous phase. The MPH–AA co‐aggregates may help to increase cellular uptake via passive diffusion by controlling the particle size to around 300 nm (Wongekalak et al ., ; Jirasripongpun et al ., ). The degree of co‐aggregation between MPH and AA was found to be dependent on their ratio and the type of carbohydrate in the bulk aqueous phase.…”
Section: Resultsmentioning
confidence: 97%
“…Our previous investigation indicated that different carbohydrate excipients used during drying of antioxidative mung bean protein hydrolysate (MPH)-asiatic acid (AA) resulted in different anticancer efficacy of AA in human hepatoblastoma HepG2 cells when MPH was used as a peptide carrier for AA. It was also found that the disaccharide lactose enhanced the cytotoxicity of MPH-AA co-aggregates compared with that of AA alone (Wongekalak et al, 2011;Jirasripongpun et al, 2012). The influence of different carbohydrates on the efficacy of MPH-AA for cellular uptake led to the suggestion that the molecular weight (MW) of the carbohydrate may influence the aggregation nature of AA and MPH-AA.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the drug administration, cytotoxicity of the compounds against host cells is needed to be evaluated ( Tharmalingam et al, 2018 ). IC 50 values for AA were reported to be greater than 100 μM (∼50 μg/ml) on human umbilical vein endothelial cells and kidney epithelial Vero cells ( Jirasripongpun et al, 2012 ; Huang et al, 2016 ), as well as no significant effect of the compound at the same concentration was observed on viability of human gastric mucosa epithelial cells ( Jing et al, 2016 ). Additionally, up to 165 mg/kg of AA was administered to the mice without any signal of side effects ( Krishnamurthy et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%